2016
DOI: 10.1074/jbc.m115.674234
|View full text |Cite
|
Sign up to set email alerts
|

Runx1 Phosphorylation by Src Increases Trans-activation via Augmented Stability, Reduced Histone Deacetylase (HDAC) Binding, and Increased DNA Affinity, and Activated Runx1 Favors Granulopoiesis

Abstract: Src phosphorylates Runx1 on one central and four C-terminal tyrosines. We find that activated Src synergizes with Runx1 to activate a Runx1 luciferase reporter. Mutation of the four Runx1 C-terminal tyrosines to aspartate or glutamate to mimic phosphorylation increases trans-activation of the reporter in 293T cells and allows induction of Cebpa or Pu.1 mRNAs in 32Dcl3 myeloid cells, whereas mutation of these residues to phenylalanine to prevent phosphorylation obviates these effects. Three mechanisms contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…HDAC1 and HDAC3 are implicated in granulopoiesis. When Runx1 is phosphorylated by Src kinase, the reduced interaction of Runx1-HDAC1/HDAC3 is relevant to increased DNA affinity and the induction of granulopoiesis [40]. Class IIa HDAC4 can be recruited to the Arg1 promoter region, which leads to a reduction in the acetylation of both histone 3 and STAT6 proteins and subsequent transcriptional activation of Arg1, resulting in monocyte and CD8α(+) conventional DC differentiation [41].…”
Section: Granulocyte-monocyte Lineage Terminal Differentiationmentioning
confidence: 99%
“…HDAC1 and HDAC3 are implicated in granulopoiesis. When Runx1 is phosphorylated by Src kinase, the reduced interaction of Runx1-HDAC1/HDAC3 is relevant to increased DNA affinity and the induction of granulopoiesis [40]. Class IIa HDAC4 can be recruited to the Arg1 promoter region, which leads to a reduction in the acetylation of both histone 3 and STAT6 proteins and subsequent transcriptional activation of Arg1, resulting in monocyte and CD8α(+) conventional DC differentiation [41].…”
Section: Granulocyte-monocyte Lineage Terminal Differentiationmentioning
confidence: 99%
“…Our work demonstrated that Tyr phosphorylation within the ID region of RUNX1 is critical for its oncogenic potential, and thus, an important next step will be to identify potential coregulatory proteins that bind to this domain. Significantly, previous studies have shown that Tyr phosphorylation impairs Meg and T cell development but increases Runx1 stability and transactivation of Cebpa in myeloid cell lines ( Huang et al, 2012 ; Leong et al, 2016 ).…”
Section: Discussionmentioning
confidence: 89%
“… 107 The reduced interaction of Runx1 with HDAC1/HDAC3 induced by Src kinase-mediated Runx1 phosphorylation is related to increased DNA affinity and the induction of granulopoiesis. 108 Furthermore, Runx1 and PU.1 independently interact with the ETO2–SIN3A–HDAC2 corepressor complex and coactivate the expression of M-CSFR and GM-CSFR, which control the development and activation of granulocyte–monocyte cells. 109 For the erythrocyte lineage, HDAC1/Sin3A can be recruited by EKLF to inhibit β-globin expression in undifferentiated EBHX11L cells, while this complex can be converted to the EKLF-p300/CBP-SWI/SNF complex and promote β-globin expression during the differentiation of EBHX11L cells to a primitive erythroid phenotype.…”
Section: Histone-modifying Cofactorsmentioning
confidence: 99%